Impact of venture competitions on entrepreneurial network development - Jung Eung Park; Jim Pulcrano; Benoît Leleux (Cogent Business & Management, 2020)
Unlike what organizers of venture competitions usually claim, we found no significant correlation between participating in venture competitions and the expansion of entrepreneurial networks for early stage entrepreneurs. We conducted a linear regression analysis with survey data from entrepreneurs in Switzerland. Participating in a venture competition requires a significant amount of time for an entrepreneur as well as resources that the start-up could use elsewhere for other critical activities. This research can help entrepreneurs decide whether or not to participate in a venture competition by specifying their expected outcomes regarding entrepreneurial networks. Organizers of venture competitions need to design programs that are appropriate to the development stages of the entrepreneurs they are targeting.
Keywords: 650; entrepreneurial networks; networking process; entrepreneurial ecosystem; venture competitions